Effects of pesticide application on soil bacteria community structure in a cabbage-based agroecosystem in Ghana - Sefa Peprah; Patrick Addo-Fordjour; Bernard Fei-Baffoe; Kwadwo Boampong; Silas Wintuma Avicor; James Damsere-Derry (PLoS ONE, 2025)
Modern sustainable agriculture often relies on pesticide application, which may unintentionally affect non-target soil microorganisms. This study assessed the effects of commonly used pesticides in cabbage cultivation on bacteria diversity, composition, and abundance in soils from some farming communities in Bosome Freho District, Ghana. The pesticides included a neonicotinoid (acetamiprid), microbial agents (Pieris rapae granulosis virus+ Bacillus thuringiensis), avermectin (emamectin benzoate), and pyrrole (chlorfenapyr). Soil samples were collected from non-contaminated (NCS), abandoned pesticide-contaminated (AB-PCS) and actively pesticide-contaminated (AC-PCS) soils. Bacteria communities were analysed in the soil at phylum, class, order, family, genus, and species levels using 16S rRNA gene sequencing. The soils were also analyzed for physicochemical properties. Our results showed a decrease in bacteria diversity and abundance in pesticide-contaminated soils in the following order: NCS > AB-PCS > AC-PCS. Sorensen’s coefficient of similarity indicated major shifts in bacteria taxa composition due to pesticide contamination. In NCS, Pseudomonas veronii, Bacillus sp., and Prevotella albensis were the most abundant species, while Rhodoplanes elegans and Nostocoida limicola dominated AB-PCS. In AC-PCS, R. elegans, Gemmata obscuriglobus, Nitrospira calida, and N. limicola were the most abundant species. The abundance of Bacillus sp., P. veronii, and P. albensis decreased in the contaminated soils, while the abundance of N. calida, Cystobacter sp., Pedomicrobium australicum and Byssovorax cruenta was higher in the contaminated soils. Key genera involved in nutrient cycling such as Clostridium, Bacillus, Prevotella, Pseudomonas, and Arthrobacter, declined in abundance in pesticide exposed soils. In contrast, an increase in abundance of various taxa such as Pedomicrobium, Hyphomicrobiaceae, Pirellulaceae, Comamonadaceae, Nitrospirales, Nitrospira, Anaerolineae, Planctomycetes, Acidobacteriaí and Nitrospirae was observed in the contaminated soils. These bacteria may possess bioremediation potential that could be exploited for environmental remediation. Soil physicochemical properties and nutrient levels varied across the three soil treatments, with potential implications for bacteria community structure.